R&D of ultra-fast 8 × 8 anodes MCP-PMT. (1st April 2022) - ,; Wu, Q.; Cao, Y.; Huang, G.; Hua, Z.; Jin, M.; Jin, Z.; Li, D.; Li, K.; Liu, S.; Ma, L.; Qian, S.; et al.
Abstract: Cooperating with the North Night Vision Science & Technology (Nanjing) Research Institute Co. Ltd, Institute of High Energy of Physics in China is developing a 2-inch square shape 8 × 8 anodes micro-channel-plate photomultiplier tube (MCP-PMT) with a time resolution of picosecond level. It has a 40 × 40 mm 2 bi-alkali photocathode with a peak quantum efficiency (QE) of about 22% around a wavelength of 410 nm. With the chevron MCP stack, the MCP-PMT can reach a gain of over 10 6   under a working voltage of 1500 V. The typical output waveform has an amplitude of 64 mV and a rise time of 334 ps. Due to the well-designed structure of the MCP-PMT, the transit time spread (TTS) for the middle anode can reach 36 ps when working at single photon mode. To evaluate the performance uniformity of the 8× 8 anodes MCP-PMT, ten anodes which constitutes the smallest repetition unit of the anode array are chosen and tested. The average transit time spread (TTS) for the 64 anodes is 44.1 ± 2.0 ps.